PENGARUH ROA, LDR, EPS DAN PBV TERHADAP RETURN SAHAM (Studi Empiris Di Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2014) - Isna Abid Faiz, 12.05.52.0218; Setyowati, Widhy (Students Journal of Accounting and Banking, 2016)
The study examined the effect of ROA, LDR, EPS and PBV on stock returns. This research was conducted at the Indonesian Stock Exchange by using analysis of banking companies that have go public. The population is banking companies listed in Indonesia Stock Exchange year period 2012-2014 using purposive sampling techniques and obtained a sample of 50. Methods of data analysis using multiple linear regression. The results showed that EPS has positive effect and significant on stock returns. ROA, LDR and PBV had no significant effect on stock returns.Keywords: ROA, LDR, EPS, PBV and Stock Returns